Diseño, construcción y puesta a punto de una barrenadora portátil de 10 HP de potencia para realizar mecanizados en Hidrosistemas Gil S.A.S (2022)
This document describes the design, construction and commissioning of a 3 HP power portable drill, which fulfills the function of machining the lifting ears of the buckets of excavators or loaders for heavy and agricultural machinery. The purpose is to manufacture a machine that is efficient and reduces operating times in the company, in the same way, that is light and has a relatively low manufacturing cost